2011
DOI: 10.1093/njaf/28.3.161
|View full text |Cite
|
Sign up to set email alerts
|

A Carbon Management Diagram for Oak-hickory Forests in Southern Ohio

Abstract: A carbon management diagram for use in oak-hickory forests in southern Ohio has been developed to allow easier quantification of total forest carbon stock. The total carbon stock is positively correlated to basal area and average stand diameter but poorly correlated to the number of trees per acre. The total amount of carbon stored in these forests is going to be influenced by age and site quality to the extent that age and site influence basal area and the average tree size. Accordingly, not all stands consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…What species to use for afforestation purposes with goals of soil rehabilitation and sequestering C should be given careful consideration. Williams and Tao ( 2011 ) found that the total forest C stock is correlated to forest density as measured by basal area, and weakly correlated to the number of trees per area. Species composition will also infl uence the forest density, thus dictating the total standing C stock.…”
Section: Considerations Of C Sequestration and Survivabilitymentioning
confidence: 96%
“…What species to use for afforestation purposes with goals of soil rehabilitation and sequestering C should be given careful consideration. Williams and Tao ( 2011 ) found that the total forest C stock is correlated to forest density as measured by basal area, and weakly correlated to the number of trees per area. Species composition will also infl uence the forest density, thus dictating the total standing C stock.…”
Section: Considerations Of C Sequestration and Survivabilitymentioning
confidence: 96%